Peran PBB sebagai Organisasi Internasional Dalam Mengatasi Konflik Rusia Dan Ukraina Demi Membangun Perdamaian Dunia - Anggita; Devi Chintya Dewi (Universitas Kuningan, 2024)
International organization is a coalition created to bring nations together in international cooperation. One of them was the United Nations, the most famous post-World War II international organization. The history of the organization began in the 19th century with the establishment of the International Communication Organization, followed by the presence of the League of Nations and the United Nations. The most important purpose of the existence of such an international organization is to bring about world peace through the international relations held between these nations. Despite the existence of international organizations, international conflicts continue, such as the Russian-Ukrainian conflict. The United Nations, which is an international organization, has played a major role in bringing about peace between Russia and Ukraine in the conflict of 2022. That then produced some important points that became decisions that had a considerable impact, albeit indirectly, on Russia for having violated international law.